Efeito das interações multi-tróficas sobre os traços morfológicos de insetos consumidores de semente - Oliveira, Tamires Camila Talamonte de (2018)
The species are interconnected through multiple ecological interactions forming complex trophic networks. The intensity of the interactions and the structures of the trophic networks have been recently associated to the body size of the organisms. Understanding how interactions can affect the morphological traits of these individuals may be important in ecological studies because these morphological features are relatively easy to measure and relate to most of the physical and biological attributes of the species. In the first article, we tested how ecological interactions affect the body size of the three most abundant species of insects of the Senegalia tenuifolia plant (Fabaceae: Mimosoideae). We estimated the body size of Merobruchus terani (Coleoptera: Chrysomelidae: Bruchinae), Stator maculatopygus (Coleoptera: Chrysomelidae: Bruchinae), and Allorhogas vulgaris (Hymenoptera: Braconidae: Doryctinae) through the length of their posterior tibias. The results of this article showed that the tibia size of each species responds differently to interactions. M. terani is the most abundant species and the one that had the greatest influence of the interactions on its body size, whereas the other two species were less abundant and showed that the influences of these interactions can be more plastic and may be negative or positive depending on the situation. We discuss how these interactions can cause these positive and negative impacts, and concluded that body size can provide important biological information in trophic network studies. In the second article, we evaluated how competition, parasitism and seed biomass affect the development of M. terani, S. maculatopygus, A. vulgaris. For this, we created categories of infestation, parasitism and seed size, and we verified how these factors affect the allometric patterns, the fluctuating asymmetry (FA) and finally the morphological traits of these species. The results of this article show that although the allometric pattern remained negative regardless of the species or categories, there were considerable variations in the values of the allometric angles among the categories, indicating that the interactions can act in the development of an organisms' form. In addition, we observed that the increase in the rate of competition and parasitism caused a greater variation in the confidence interval generating greater variability in the allometric relation in these cases. Moreover, although we did not observe the effect of the categories on FA of these insects, we verified considerable changes in the morphological structures, evidencing that this measurement is the most appropriate in studies focused on interaction and morphometry. Finally, we suggest that although species play the same ecological role, they respond differently to interactions.